Effect of supplementation of substrate with brans and oil cakes on yield of oyster mushroom (Pleurotus spp.) - S. KUMAR, J.P. SHARMA* and (Indian Phytopathology, 2009)
Straw based substrate requires supplementation of brans or oil cakes for optimization of CN ratio which help in increasing productivity of mushroom. Accordingly, experiment was conducted on three oyster mushrooms viz; Pleurotus florida, P. sajor-caju and P. ostreatus with supplementation of brans (wheat and rice), oil cakes [Indian beech (karanj) Deris indica and de-oiled soybean flour (Glycine max)] in the paddy straw substrate. Use of supplements in the substrate resulted into significant increase in yields of fruiting bodies of all the three species of Pleurotus. Supplementation with wheat bran @2% enhanced the yield significantly in P. florida (48.3%), P. sajor-caju (44.9%) and in P. ostreatus (48.1%) over control. The yield of P.ostreatus was higher (52.9%) at 4% wheat bran supplementation but this increase was statistically at par with that of 2% level. Similar trend was obtained with 2% rice bran supplementation Use of de-oiled soybean supplements P.florida showed 31.3% decrease in yield. Similarly < 10% yield decline was noted in P.sajor caju with the use of karanj cake. Combination of all supplements was most beneficial to increase yield in P. ostreatus 54.7%. Thus the wheat bran @2% (w/w) supplementation was found beneficial in increasing the yield.